A randol\fised controlled trial on endotracheal tube-proseal laryngeal mask exchange and awake extubation with lidocaine during emergence of anaesthesia in controlled hypertensive patients undergoing elective surgery in Hospital Universiti Sains Malaysia - Foong Kit, Weng (2008)
A randomised controlled trial on endotracheal tube (ETI')-Proseal laryngeal mask (PLMA) exchange and awake extubation with lidocaine during emergence of anaesthesia in controlled hypertensive patients undergoing elective surgery in Hospital Universiti Sains Malaysia Objectives: The aim of this study was to compare the use of ETI-PLMA exchange and awake extubation with lidocaine in the attenuation of the cardiovascular response and respiratory complications among hypertensive patients. A substudy of the effects of beta blocker antihypertensive 1herapy on the haemodynamic changes of both groups will also be explored. Methodology: A total of 62 controJied hypertensive patients were recruited. Standard anaesthetic management was provided during the preoperative and intraoperative period. Thirty one patients were placed in group 1 where awake extubation was performed after a 2 minutes prior dose of N Lidocaine I mg.kg"1 while the other 31 patients were placed in group 2 where a PLMA was inserted in deep plane of anaesthesia replacing EIT before emergence of anaesthesia. Neostigmine and glycopyrrolate were chosen as the choice of reversal. Haemodynamic changes consisting of systolic, diastolic and mean arterial blood pressure, heart rate and rate pressure product were charted on arrival to the operation theatre (baseline~ at removal ofETI or P~ at 1, 2, 3, 5 and 10 minutes after airway removal. Incidence of respiratory complications was noted. Haemodynamic variables were analysed by repeated measures ANOV A foJiowed by paired and independent t-test while respiratory complication data by Chi-square <:l) test Subset of patients with beta blocker therapy were analysed to assess its haemodynamic eftects. Results: Demographic data were comparable in all groups. There was no difference in the baseline haemodynamic parameters. Group 1 subjects demonstrated an immediate and significant increase in SBP, DBP, MAP, HR and RPP while Group 2 subjects haemodynamic variables showed an initial slight insignificant rise. There was a significant difference in the haemodynamic parameters between group 1 and 2. Presence of beta blocker therapy reduced slightly the baseline haemodynamics and blood pressure changes over the 10 minutes measurement A significant difference persisred in the BP measurements between group I and 2 treated with beta blocker. Measured heart rates were lower and stable resulting in a lower and favourable RPP index. Smooth emergence with minimal minor respiratory complications was noted in 93.5% ofETI-PLMA group subjects as compared to 87.1% in lidocaine group. No m~or respiratory complication was noted. Conclusion: ETI-PLMA exchange is a safe and easy procedure that provides a bridge to smoother emergence with a secure airway. It is superior in attenuating the haemodynamic response to emergence of anaeSthesia with least haemodynamic variability compared to lidocaine lmg.kg-1 in hypertensive patients. Treatment with long tenn beta blocker offer little additional blood pressure lowering effect in the presence of IV Lidocaine and usage of E1T -PLMA for emergence but was able to ensure a lower and stable heart rate resulting in a lower RPP index (<12,000) especially in the IV Lidocaine group